AB041. Case report of extrinsic allergic alveolitis with a “headcheese” CT pattern - Rampiadou, Christina (Ann Transl Med, 2016)
The description of a case of extrinsic allergic alveolitis. An eighty-year-old female was admitted because of breathlessness and fatigue for the past 15 days. Accompanying diseases: rheumatoid arthritis on methotrexate and hydroxychloroquine and arterial hypertension. She reported exposure to mould inside the room she was sleeping (her relatives scratched and repainted the walls of the room recently). Physical examination revealed velcro sounds on both lung bases. WBC: 10.7 (78–17–4), ESR 58, CRP 7.9, BNP 128 (<100), Lac 4.8 (<1.6). ABG’s pH 7.43, pCO(2) 28 mmHg, pO(2) 48 mmHg. Echocardiography revealed normal left ventricle and intraventicular septum, EF 55–60%, small increase of left atrial dimensions, MR1+ TR1+, E < A. She was put on piperacillin—tazobactam. A day later the chest HRCT revealed small pleural effusions on both pulmonary bases, “headcheese” sign (thickening of interlobular and intralobular septae superimposed on a mosaic pattern of ground glass attenuation and multiple areas of consolidation and air trapping), a pattern compatible with extrinsic allergic alveolitis. She was put on corticosteroids (methylprednisolone 120 mg/day) and she quickly improved. She was released on 32 mg per day after 8 days of hospitalization. Spirometry: FEV1 0.76 L (43%), FVC 0.79 L (36.5%), DlCO 10.13 (60%), TLC 1.29 L (27%). Five months later the spirometry was normal FEV1 1.65 L (123%), FVC 1.89 L (112%), DLCO 10.13 (60%), TLC 2.76 L (63%) and the new chest CT revealed disappearance of the pleural infusions and the crazy paving pattern. Corticosteroids were gradually withdrawn and since then she remains asymptomatic and in a good condition. The grave initial clinical condition of the patient did not allow the performance of a BAL, and the serum precipitins could not be measured in our city. The characteristic image of “headcheese” in conjunction with the exposure history to mold made the diagnosis of extrinsic alveolitis most likely and guided therapeutic decisions.